Develop on Yammer : social integration for modern business applications - Rawal, Pathik; Rohilla, Pryank (Expert's voice in Yammer., 2015)
Develop on Yammer is your guide to integrating the Yammer social network with your company's application ecosystem. By developing custom apps and features on the Yammer platform, you can make your workplace more productive, encourage communication and feedback, and get your colleagues collaborating across a range of platforms, including SharePoint, ASP.NET, and Windows Phone. The book begins with an introduction to the development options available along with guidance on how to set up a Yammer developer account. You'll then take your first step in Yammer integration by building a Yammer feed into a web page or other JavaScript-based client application, before diving into app creation and management on the Yammer platform. The authors provide a deep dive into the Yammer authorization process from client-side and server-side perspectives, and you'll find out how to work closely with Yammer's data streams and its full range of development possibilities using Open Graph and Yammer's REST API. The final chapters cover how to build Yammer integration into standalone applications for SharePoint and Windows Phone 8 with Yammer SDKs. All chapters are illustrated with examples and sample code, and a case study follows the development of a workplace training application as the authors apply each technique, so you can see how to make the most of what Yammer has to offer. What You'll Learn Why develop on Yammer, and what development options are available How to add a Yammer feed to an HTML-based application using Yammer Embed, to bring relevant news and discussions into the contexts where they matter How to develop custom Yammer features for your SharePoint, Office or web applications on the client side with the Yammer JavaScript SDK How to carry out secure authorization and authentication on Yammer How to use Yammer Open Graph and REST APIs to posts messages, create custom activities and get data from Yammer-integrated applications How to work with the Yammer Windows Phone 8 SDK to add Yammer functionality to a Windows Phone 8 application Who This Book Is For This book is targeted at developers with a background in .NET/C♯ development. Readers should be comfortable working with JavaScript. Software architects will also find this book valuable for planning social integration across their companies' business ecosystems.